Impaired insulin sensitivity is associated with worsening cognition in HIV-infected patients. (19th March 2019) - Khuder, Saja S.; Chen, Suming; Letendre, Scott; Marcotte, Thomas; Grant, Igor; Franklin, Donald; Rubin, Leah H.; Margolick, Joseph B.; Jacobson, Lisa P.; Sacktor, Ned; D'Souza, Gypsyamber; Stosor, Valentina; et al.
Abstract : Objective: To determine the association of insulin sensitivity and metabolic status with declining cognition in HIV-infected individuals. Methods: We conducted targeted clinical and metabolic measures in longitudinal plasma samples obtained from HIV-infected patients enrolled in the Central Nervous System HIV Anti-Retroviral Therapy Effects Research Study (CHARTER). Findings were validated with plasma samples from the Multicenter AIDS Cohort Study (MACS). Patients were grouped according to longitudinally and serially assessed cognitive performance as having stably normal or declining cognition. Results: Patients with declining cognition exhibited baseline hyperinsulinemia and elevated plasma c-peptide levels with normal c-peptide/insulin ratios, suggesting that insulin production was increased, but insulin clearance was normal. The association of hyperinsulinemia with worsening cognition was further supported by low high-density lipoprotein (HDL), high low-density lipoprotein/HDL ratio, and elevated cholesterol/HDL ratio compared to patients with stably normal cognition. Conclusions: These findings suggest that hyperinsulinemia and impaired insulin sensitivity are associated with cognitive decline in antiretroviral therapy–treated HIV-infected patients.